LINGUODIDACTIC AND THEORETICAL-METHODOLOGICAL FOUNDATIONS OF FOREIGN LANGUAGE TEACHING THROUGH DIGITAL APPLICATIONS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article focuses on the effectiveness of digital technologies in language learning today.It explores how digital tools can increase motivation in language acquisition, accelerate the learning process, and enhance students’ cognitive and educational engagement in modern conditions. The article also discusses innovative forms of education aimed at improving the quality and efficiency of teaching.